Physical properties, antimicrobial activity and in vivo tissue response to apexit plus - Hoshino, Roberto Alameda [UNESP]; da Silva, Guilherme Ferreira [UNESP]; Delfino, Mateus Machado [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP]; Sasso-Cerri, Estela [UNESP]; Filho, Idomeo Bonetti [UNESP]; Cerri, Paulo Sérgio [UNESP] (MDPI, 2020)
We investigated the physical properties, antimicrobial activity, and tissue reaction to Apexit Plus in comparison to Sealapex. Flow, radiopacity, setting time, and solubility were evaluated in each material. The antimicrobial activity against Enterococcus faecalis was performed. Polyethylene tubes containing Apexit Plus or Sealapex, and without material (control group) were implanted into the subcutaneous tissue of rats. At 7, 15, 30, and 60 days of implantation, the specimens were paraffin-embedded and the number of inflammatory cells (ICs) and the amount of birefringent collagen (BC) were quantified. The von Kossa reaction followed by immunohistochemistry for detection of alkaline phosphatase (ALP) was also performed. Statistical analysis was performed with ANOVA and Tukey test (p ≤ 0.05). The flow value of Apexit Plus was greater than Sealapex, whereas the radiopacity (3.44 mm Al) was lower than Sealapex (6.82 mm Al). Apexit Plus showed lower solubility and shorter initial and final setting (p < 0.0001), whereas the antimicrobial activity was significantly greater than Sealapex. Although the number of ICs was higher in Apexit Plus (p = 0.0009) at 7 days, no significant difference was detected between Apexit Plus and Sealapex at 15, 30, and 60 days. All groups showed higher values for BC in the capsules over time. ALP-immunolabelled cells were observed, mainly around von Kossa-positive structures, either in the capsules of Apexit Plus or Sealapex. Therefore, our results revealed that Apexit Plus exhibited a greater effectiveness against Enterococcus faecalis and better physical properties than Sealapex, except for the radiopacity. In vivo findings indicate that Apexit Plus is biocompatible and presents potential bioactivity in the subcutaneous tissue.
Keywords: Alkaline phosphatase; Bioactivity; Biocompatibility; Enterococcus faecalis; Immunohistochemistry; Sealers